Between the tides in Washington and Oregon : exploring beaches and tidepools - Kelly, Ryan P. (Ryan Patrick); Klinger, Terrie, 1956-; Meyer, John J. (University of Washington Press, 2022)
"In the intertidal zone-the space between low and high tide-a rich and complex ecosystem thrives. It's an easily overlooked space, but the porcelain crabs, ochre stars, and other curious species that call this place home provide a window into the hidden workings of the natural world. Drawing on the authority of two leading scientists and the storytelling power of a science writer, this guidebook to the coasts of Washington and Oregon offers general readers a highly-accessible overview of the rich and surprising ways that water and land interact to create seashore ecologies. The authors systematically take readers along the coast, highlighting what makes each location fascinating and unique. (For example, pointing out where to find bioluminescent dinoflagellates, the single-celled algae that light up and trace any disturbance in the shallow water.) At the heart of this richly-illustrated book is a desire to help readers understand the scientific forces that shape the plants, animals, and landscapes at each location; it's the essential guidebook to keep in the car for the reader who wants to know why"--